Plan de negocios para la creación de una empresa productora y comercializadora delivery de alimentos dietéticos en la ciudad de Latacunga. - Parra Trávez, Eric David (2020)
The business plan for the creation of a home service company that produces and sells diet foods in the city of Latacunga, was carried out based on the limited supply of healthy food for the inhabitants of the town, specifically in the urban area for people working in the public and private area. It was developed with the purpose of knowing the viability of the project during the five years of the proposal horizon. Likewise, the business plan that helps to determine various activities that the company must carry out in areas such as: market, technical, organizational and financial was used as a methodology for the investigation. For the collection of primary information, a survey of a total of 361 people representing the sample was used. The type of sampling is non-probabilistic, where the habits, tastes and preferences of potechintial clients were analyzed. In the technical area, the processes and activities were used for the preparation of the menus were established, on the other hand, the structural outline of how the organization will be made and the functions that the employees must fulfill are made. Finally, in the financial study, the feasibility of the business was obtained as a result of the main evaluation indicators such as the internal rate of return, which is 51%, while the net present value amounted to $9.520,50, the net profit for the year for the five years is positive and has increases in each period.